A quantitative evaluation of judicial justice in civil cases with Chinese free trade zone enterprises as the plaintiff - Yutian Jiang; Na Zhang (Heliyon, 2023)
Justice is the primary criterion for evaluating the law. Chinese free trade zones aim to attract foreign investment and promote economic development efficiency, but their judicial reform goal still needs to be justice. Given the importance of balancing justice and efficiency, this study assesses whether the judiciary sacrifices justice for the sake of economic efficiency in civil cases with Chinese free trade zone enterprises acting as the plaintiff. By introducing commercial factors such as enterprise subject and legal resource characteristics into a theoretical model, this study develops a hierarchical regression model to investigate the judicial process in free trade zones. This study statistically analyzes data from judgments and enterprises' public information, quantitatively evaluating the realization of judicial justice. This study finds: First, plaintiffs’ violated rights and interests have been protected and compensated, that is, the judicial result has been just; Second, judicial practice in this field has the characteristics of neutrality, equality, participation, and openness and adheres to the principle of “the same case has the same judgment”, that is, the judicial procedure has been just. Accordingly, this study argues that judicial justice has not given way to economic efficiencies, such as attracting foreign investment, in cases with Chinese free trade zone enterprises as the plaintiff.